Physical activity and risks of breast and colorectal cancer: a Mendelian randomisation analysis - Nikos Papadimitriou (Nature Portfolio, 2020)
Physical activity has been linked to lower risks of colorectal and breast cancer. Here, the authors present a Mendelian randomisation analysis supporting a potentially causal relationship between higher physical activity levels and lower risks of breast cancer and colorectal cancer.